Comparative evaluation of the aqueous and ethanolic extracts of Erythrina mulungu: Chemical composition and biological activities (Research, Society and Development, 2026)
Plant extracts are widely used as sources of bioactive compounds, especially phenols, flavonoids, and alkaloids, whose extraction depends directly on the type of solvent employed. This study aimed to compare the aqueous and ethanolic extracts obtained from the bark of Erythrina mulungu, evaluating their chemical and functional characteristics through High-Performance Liquid Chromatography (HPLC), Fourier Transform Infrared Spectroscopy (FTIR), total phenolic content, antimicrobial activity, and antioxidant activity analyses. The aqueous extract showed lower chemical diversity and reduced bioactivity, with a phenolic content of 7.64 mg GAE/g, antimicrobial halos smaller than 14 mm, and 14.70% inhibition in the DPPH assay. In contrast, the ethanolic extract exhibited a more complex composition, with chromatographic peaks associated with erythrinic alkaloids and lipophilic phenols, as well as additional FTIR bands consistent with carbonyls, ethers, and amines. This extract presented a phenolic content of 729.68 mg GAE/g, halos of 21.50 mm (E. coli) and 35.75 mm (S. aureus), and high antioxidant activity (92.82%). The results demonstrate that ethanol promotes a more efficient extraction of bioactive metabolites, whereas the aqueous extract shows a more restricted composition. Thus, solvent selection directly influences the chemical profile and biological performance of Erythrina mulungu extracts, reinforcing the importance of choosing an appropriate extraction method in phytochemical studies.